The Insertion of Electrodes in the Brain for Electrophysiological Recording or Chronic Stimulation Is Not Associated With Any Biochemically Detectable Neuronal Injury. Issue 5 (10th April 2017) - Themistocleous, Marios S.; Sakas, Damianos E.; Boviatsis, Efstathios; Tagaris, George; Kouyialis, Andreas; Psachoulia, Christina; Stathis, Pantelis
Abstract : Objective: The aim of this study was to evaluate the degree of brain tissue injury that could be potentially induced by the introduction of a) microrecording electrodes, b) macrostimulation electrodes, or c) chronic stimulation electrodes. We aimed to evaluate whether the use of five simultaneous microrecording tracks is associated with any brain injury not detectable by conventional imaging such as CT or MRI. Materials and Methods: The study included 61 patients who underwent surgery for implantation of 121 DBS leads. In all cases, five simultaneous tracts were utilized for microelectrode recordings. All patients underwent measurements of serum S‐100b at specific time points as follows: a) prior to the operation, and b) intraoperatively at specific stages of the procedure: 1) after opening the burr hole, 2) after the insertion of microrecording electrodes, 3) during macrostimulation, 4) at the end of the operation, and 5) on the first postoperative day. Results: The levels of serum S‐100B protein remained within the normal range during the entire period of investigation in all patients with the exception of two cases. In both patients, the procedure was complicated by intraparenchymal hemorrhage visible in neuro‐imaging. The first patient developed a small intraparenchymal hemorrhage, visible on the postoperative MRI, with no neurological deficit. The second patient experienced a focal epileptic seizure after the insertion of the right DBS chronic lead and the postoperative CT scan revealed a right frontal lobe hemorrhage. Conclusion: These results strongly indicate that the insertion of either multiple recording electrodes or the implantation of chronic electrodes in DBS does not increase the risk of brain hemorrhage or of other intracranial complications, and furthermore it does not cause any biochemically detectable brain tissue damage.